PENGARUH MODEL KOOPERATIF TIPE GI TERHADAP HASIL BELAJAR PKN DI SEKOLAH DASAR - Nurinsani, Nurinsani; Taufik, Taufina; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the research was to know about the influence of using of cooperative group investigation  type model toward the result of PKn student in grade V at SDN 20  Lubuk Alung. The research design of the research is quasy exsperimental design. Sample of the research is class VA and VB. The coubting result of research of data that used is t test founded t count > ttable , t-test 2,36 > 1,68  at α level of 0.05. So that, it can be concluded that there is a significant influence in using cooperative model in jigsaw type toward the result of student’s PKn study in grade V SDN  20 Lubuk Alung . Keywords: Cooperative type group investigation, Learning Outcome, PKn